(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the phenomenon of ellipsis as a core feature of linguistic economy in modern Uzbek. The study investigates how ellipsis operates in both written and spoken discourse, focusing on its syntactic, pragmatic, and stylistic functions. Through descriptive and comparative analysis, the article outlines the structural characteristics of ellipsis in Uzbek, its communicative motivations, and its role in achieving clarity, brevity, and coherence in communication. Drawing on theoretical frameworks from functional grammar and discourse analysis, the study highlights ellipsis as a pragmatic tool that reflects the cognitive and social dynamics of language use.